U tornar-si negra a parti d’uma cosmupercepção africana sobri u trabalhu: uns paranauê interseccional i decolonial - Mesquita, Juliana Schneider (2021)
This dissertation aimed to analyze how the process of becoming Black woman enables alternative ways to think about the nature of work from an African cosmoperception. My proposal was to understand this phenomenon from an Afro-centered decolonial endoperspective, evoking my place of speech as a Black woman in a constant process of becoming Black. To do so, I use African cosmoperception and the theoreticalmethodological apparatus of decoloniality and intersectionality (focus on gender and race), and Afro-centered research methods to produce data - the escrevivências1 - and for the analysis of the data - the Analysis Decolonial Discourse Critique (ADDC). I chose as a field of research the Blogueiras Negras (BN) website, as the subjects participating in this research were self-declared black women who published their escrevivências2 on this blog. In all, 25 escreviventes3 were selected who wrote 26 escrevivências4 , from which 34 causos5 were selected to compose the corpus of analysis. The main results of this study pointed to six typifications of coloniality strategies: 1) the schizophrenic; 2) the antagonist; 3) the prisoner; 4) the exile; 5) the imposter; and 6) the fool. And for six typifications of resistance to decolonity: 1) convinced; 2) the protagonist; 3) the subversive; 4) the quilombola; 5) the Afrocentric; and 6) the intellectual. This study demonstrated that, based on escrevivências6 , Black women can look at their own experiences (permeated by intersectionalities of gender and race), think and analyze their practices and, based on them, use this knowledge to organize, problematize, act, experiment and to think of other ways of being and living in which black women feel that they are protagonists of their history. The process of becoming Black woman involves a complex range of works involved by relations of power-know-being that make it possible to rethink the nature of work usually used in the field of Organizational Studies, which under a Western-centric cosmovision reduces it to a capitalist bio-logic, which relegates other forms of work to a non-work status.